Prognostic significance and relationship of worst lead residual ST segment elevation with myocardial damage assessed by cardiovascular MRI in myocardial infarction. Issue 16 (4th June 2014) - Rommel, K P; Baum, A; Mende, M; Desch, S; Gutberlet, M; Schuler, G; Thiele, H; Eitel, I
Abstract : Objective: To investigate the relation of residual worst lead ST segment elevation (WL-STE) after ST segment myocardial infarction (STEMI) with infarct size and microvascular injury assessed by cardiovascular magnetic resonance (CMR) imaging. Background: WL-STE in patients with acute reperfused STEMI has been shown to identify high risk patients for major adverse cardiovascular events (MACE). However, the relation of WL-STE with myocardial damage is unknown. Methods: In this multicentre study we analysed ECG data 90 min after primary percutaneous coronary intervention (PCI) in 763 STEMI patients. WL-STE was defined as the absolute magnitude of STE in the most affected lead on the post-PCI ECG. Patients were categorised into three groups (<1 mm, 1–2 mm, and ≥2 mm). CMR was performed within 1 week after infarction for comprehensive assessment of myocardial damage using a standardised protocol. The primary clinical endpoint was MACE defined as death, reinfarction, and new congestive heart failure within 12 months after infarction. Results: WL-STE <1 mm, 1–2 mm, and ≥2 mm was present in 155 (20%), 328 (43%), and 280 (37%) patients, respectively. Myocardial damage determined by CMR demonstrated a graded relationship of infarct size (median (IQR) 13.3 (6.2–20.3)%LV vs 13.7 (7.6–21.3)%LV vs 22.5 (15.6–31.2)%LV, p<0.001), the myocardial salvage index (60.8 (37.0–84.5) vs 55.0 (36.6–73.9) vs 42.7 (26.2–58.2), p<0.001), and microvascular obstruction (0.0 (0.0–0.9)%LV vs 0.0 (0–1.0)%LV vs 1.2 (0.0–3.6)%LV, p<0.001) across the three groups. WL-STE ≥2 mm was strongly associated with MACE 12 month after infarction (HR 1.93, 95% CI 1.11 to 3.37; p=0.02). Conclusions: This largest CMR study to date correlating post-PCI WL-STE with markers of myocardial damage demonstrates that WL-STE is significantly associated with infarct size, myocardial salvage, microvascular obstruction, and MACE in a high risk STEMI population. Trial registration number: NCT00712101.